2022
DOI: 10.26803/ijlter.21.2.13
|View full text |Cite
|
Sign up to set email alerts
|

Filipino Teachers’ Attitudes towards Distance Learning during the Covid-19 Pandemic

Abstract: Due to the impact of the COVID-19 pandemic, distance education has subsequently turned into the dominant mode of teaching, especially in the Philippines, where the majority of schools are still physically closed. Over a year since distance education was fully implemented in the country, it is essential to understand the general attitudes towards distance learning of Filipino teachers who have been teaching at various educational levels, including elementary, secondary, and tertiary levels, particularly in term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…These findings were supported by several studies that were also conducted during the pandemic. The study conducted by Bautista et al (2022), which examined the attitudes of Filipino teachers towards distant learning, revealed that, on the whole, teachers had a negative attitude towards distance learning. Also, Firmansyah and Bandono's (2022) study also revealed that addressing the issue of teacher motivation during the pandemic necessitates a focus on enhancing teachers' professional teaching competences.…”
Section: 2factors That Contributed To the Difficulties Encounteredmentioning
confidence: 99%
“…These findings were supported by several studies that were also conducted during the pandemic. The study conducted by Bautista et al (2022), which examined the attitudes of Filipino teachers towards distant learning, revealed that, on the whole, teachers had a negative attitude towards distance learning. Also, Firmansyah and Bandono's (2022) study also revealed that addressing the issue of teacher motivation during the pandemic necessitates a focus on enhancing teachers' professional teaching competences.…”
Section: 2factors That Contributed To the Difficulties Encounteredmentioning
confidence: 99%